Analisis emisi gas buang kendaraan bermotor (angkutan umum penumpang) di Kabupaten Manokwari - Hendri Irnawan Saputro; Eko Agus Martanto; Umi Yuminarti (Cassowary, 2022)
Transportation is very instrumental directly in the process of development, due to the transportation community easily perform the displacement from a site to the other, thus accelerating the growth of the economy in large cities and villages. However, such transport is not feasible and provide negative impact to the environment in the form of air pollution. The purpose of research was to (1). analyse large concentrations of CO, HC, CO₂ and O₂ in the emission gas exhaust, (2). analyse the effect of emission gas exhaust of vehicles public transport, and (3) analyse the influence of the characteristics of public transport vehicles against the concentration of CO and HC test emissions existed in the District Manokwari. The research was a kind of quantitative research where all the data needed for the analysis were obtained directly. The data directly required were data obtained by measuring the amount of emission, the characteristics of the operational public transport, interviews, and analysis of regression linear multiple by using SPSS 25. The results of the study showed that the average amount of emission gas exhaust of public transport vehicles in the District Manokwari is CO at 2.13 %, HC at 534.60 ppm, CO₂ at 12.96% and O₂ at 2.71%. Most of the public transport operating in the city of Manokwari issued emission gas exhaust exceeded the threshold limit that has been set and has the potential to pollute the air or do not pass the test of emissions by 63.50% and only 36.5% in transport public passed the test of emission gas exhaust. In addition, the results of the test emission coefficient of the regression were simultaneously throughout the variables affecting the emission of CO and HC.